Development of a Web-Based Reporting System for PJLP Tasks at Dinas Pertamanan dan Hutan Kota Using the Waterfall Method - Rusdiyanto Rusdiyanto; Ade Putra Prima Suhendri (PT. ALRCA INOVASI DIGITAL, 2026)
This study has successfully developed a task reporting system for PJLP Dinas Pertamanan dan Hutan Kota, a service company specializing in park cleaning and maintenance in DKI Jakarta. Previously, the company faced difficulties in recording and tracking task reports because the system used was prone to errors and inefficient. This study focuses on developing a more effective and efficient system for managing task reports. The Waterfall method was employed, allowing for a quick and flexible response to changing needs. The system was designed as a web-based platform to enable access to asset information from various locations and at any time, in line with current demands for mobility and flexibility. The system’s performance was tested using the Department of Parks and Urban Forests as a case study, and the results demonstrated a significant improvement in task reporting, as well as increased employee work efficiency. With the implementation of this system, the City Parks and Forests Department has successfully improved efficiency in terms of time savings and achieved more structured and flexible data accuracy. This research provides tangible benefits to the City Parks and Forests Department and contributes to the development of data technology, particularly in report data management using the Waterfall approach.